Description of Porphyrosela arachisella sp. nov. (Lepidoptera: Gracillariidae), the first report of Lithocolletinae for Brazil - Fochezato, Júlia; Brito, Rosângela; Gonçalves, Gislene L.; Specht, Alexandre; Becker, Vitor O.; Moreira, Gilson R.p. (Zootaxa, 2022)
During a recent survey of leaf-mining microlepidoptera in the Cerrado biome, mines of an undescribed Porphyrosela Braun (Lepidoptera: Gracillariidae: Lithocolletinae) were found associated with the forage peanut, Arachis pintoi Krapov. & W.C. Greg. (Fabaceae). Consequently, adults, immature stages and the leaf mine of Porphyrosela arachisella sp. nov. are herein described based on light and scanning electron microscopy. A preliminary analysis of DNA barcode sequences including putative members of other lithocolletine species and all BINs (Barcode Index Numbers) available for Porphyrosela supports P. arachisella as an independent cluster, with 8 to 11% divergence. Its nearest neighbour was the cluster formed by three BINs (BOLD: ADT2137, BOLD: AAG1161 and BOLD: ADU9985) that includes specimens from Australia, Vietnam and Bangladesh. This is the first report of a lithocolletine gracillariid for Brazil, and the third species recognized for the genus in the Neotropical region.